The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1128/jcm.41.7.2952-2960.2003
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Rickettsiae by groEL Gene Analysis

Abstract: The nucleotide sequences (534 to 546 bp) of the groEL gene, which encodes the 60-kDa heat shock protein GroEL, from 15 rickettsial strains were determined and compared. In the phylogenetic tree created by the unweighted pair group method with arithmetic averages and the neighbor-joining method, rickettsial strains could be distinguished from Ehrlichia strains. Five spotted fever group strains, four typhus group strains, and six scrub typhus group (STG) strains were differentiated as distinct entities. Unlike g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 17 publications
1
25
0
Order By: Relevance
“…1,400 nucleotide sequences (8). Phylogenetic analysis based on the heat shock operon (groESL) has also been developed and was useful for the characterization and identification of Anaplasmataceae (16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1,400 nucleotide sequences (8). Phylogenetic analysis based on the heat shock operon (groESL) has also been developed and was useful for the characterization and identification of Anaplasmataceae (16).…”
mentioning
confidence: 99%
“…Recently, the partial groEL gene was used to identify Borrelia and rickettsiae (8,9). The groEL genes, which encode the 60-kDa heat shock protein GroEL, are ubiquitous in both prokaryotes and eukaryotes and encode highly conserved housekeeping proteins, which are essential for cell survival.…”
mentioning
confidence: 99%
“…GroEL gene sequences have higher degrees of divergence among the rickettsiae, and they have been proven to be able to facilitate the rapid diagnosis of rickettsial diseases and differentiate rickettsial diseases from other acute febrile diseases. 8,9 In the present study, the phylogenetic tree of groEL gene sequences forms two clusters of It has been reported that the virulence of O. tsutsugamushi is related to its serotype or genotype. 19 However, serotyping is time-and labor-consuming, and it is limited by the need to include all prototype strains when testing a new strain.…”
Section: Discussionmentioning
confidence: 99%
“…The phylogenetic analysis was performed with nucleotide sequences of the O. tsutsugamshi groEL gene and the 56 kDa gene as described by others. 8,12 Immunofluorescence assay. We obtained acute-phase anticoagulated serum from each of 52 patients and six convalescent-phase sera.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation